معوقات الاتصال والتنشيط لدى جمعية الإحسان -عزابة في ظل جائحة كرونا - أوغيدي, جهيدة; بلخيري, كمال (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى إبراز معوقات الاتصال والتنشيط لدى الجمعيات الخيرية المحلية في ظل جائحة كورونا. فالاتصال يعد محور العلاقات الاجتماعية والتنظيمية، والجمعيات واحدة من التنظيمات الاجتماعية التي تحتاج للاتصال للقيام بمهامها لتنمية المجتمع وتحقيق أهدافها. وجمعية الإحسان عزابة واحدة من الجمعيات المحلية الناشطة في مجال نقل الجنائز وإعانة المرضى ذوي الأمراض المزمنة مثل السكر والسرطان وذوي الاحتياجات خاصة الأطفال، بترميم بعض بيوت هذه الأخيرة وتقديم الأدوية والكراسي المتحركة والاتصال بالأطباء لمساعدة المرضى أو القيام بالقوافل الطبية والتنقل إلى بعض الحالات الخاصة أو المعزولة وغيرها وتلبية حاجاتهم. استخدمنا في دراستنا المنهج الوصفي لتحليل الظاهرة وتفسيرها لأنه المنهج المناسب لهذه الدراسة، واستخدمنا المسح الشامل لأعضاء الجمعية. وقد توصلت نتائج الدراسة إلى وجود معوقات في الاتصال والتنشيط لدى الجمعيات خلال فترة كورونا. This study aims to highlight the obstacles to communication and animation of local charities in the shadows of the Corona pandemic. Communication is the focus of social and organizational relations, and associations are one of the social organizations that need communication to do out their activities to develop society and achieve their objectives. Al-Ihssan Association is one of the local associations active in the field of funeral transportation and helping patients with chronic diseases such as diabetes, cancer, and those with special needs children, by renovating some of the latter's homes, providing medicines and wheelchairs, contacting doctors to help patients, carrying out awareness campaigns, and moving to some special or isolated cases and others to help them. And meet their needs. We used in our study the descriptive approach to analyze and interpret the phenomenon because it is the appropriate approach for this study, and we used the comprehensive survey of the members of the association. The results of the study found that there were obstacles to communication and animation during the corona period.
مقال
Keywords: الاتصال ; التنشيط ; الجمعيات ; معوقات الاتصال ; جائحة كورونا; communication; animation; associations; obstacles to communication; corona pandemic